Sustainable Water Desalination Using Solar-Powered Nanofluid-Based Evaporation Systems - Yusuf Wahyu Setiya Putra; Kanafi Kanafi; Fatkhurrochman Fatkhurrochman (Green Engineering: International Journal of Engineering and Applied Science, 2024)
This study explores the use of graphene-based nanofluids in enhancing the performance of solar-powered desalination systems. A laboratory-scale desalination system was developed to simulate the evaporation process, powered by solar energy, with the integration of graphene-based nanofluids to improve thermal efficiency. The experimental setup measured evaporation rates, energy consumption, and temperature profiles under varying solar radiation conditions (400–800 W/m²). Results revealed that the system with nanofluids demonstrated up to a 35% increase in evaporation rates compared to the baseline system without nanofluids, indicating enhanced heat transfer properties. Moreover, energy consumption was reduced by up to 20%, highlighting the improved energy efficiency of the system with nanofluids. The system with nanofluids exhibited higher temperatures in the evaporator, confirming more effective thermal utilization. Statistical analyses, including t-tests and regression analysis, confirmed the significant impact of nanofluids on both evaporation rates and energy consumption. This study demonstrates that graphene-based nanofluids offer a sustainable and energy-efficient solution for solar-powered desalination, particularly in areas with abundant solar radiation. The integration of nanofluids not only enhances the efficiency of the desalination process but also reduces operational costs, making it a promising alternative for addressing water scarcity in a sustainable manner. Further research is needed to optimize nanofluid formulations and assess their long-term feasibility for large-scale applications.